2016
DOI: 10.4238/gmr.15027796
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance-based study reveals the metabolomics profile of nasopharyngeal carcinoma

Abstract: ABSTRACT. Proton nuclear magnetic resonance ([1 H]-NMR) spectroscopy has been used to investigate metabolites in serum and several types of tissue. We used NMR spectroscopy to explore the differential metabolic profiles in serum from nasopharyngeal carcinoma (NPC) patients. Moreover, metabolites with potential as biomarkers for identifying NPC patients were primarily identified. Serum samples were collected from 40 enrolled participants comprising 20 healthy subjects and 20 NPC patients. Samples were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…The reason for this phenomenon is still unclear. Other research has shown that choline level in NPC patients is significantly higher than that in normal control so as to maintain the integrity of cell membrane [18, 41]. Interesting, our results from NPC cells don’t fully agree with this view, and the opposite direction seems to be more rational.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The reason for this phenomenon is still unclear. Other research has shown that choline level in NPC patients is significantly higher than that in normal control so as to maintain the integrity of cell membrane [18, 41]. Interesting, our results from NPC cells don’t fully agree with this view, and the opposite direction seems to be more rational.…”
Section: Discussioncontrasting
confidence: 84%
“…For example, Yi et al demonstrated that gas chromatography-mass spectrometry-based metabolomics analysis could identify stages of NPC subjects via metabolic profiling, and possible therapeutic outcome were evaluated through certain metabolites alterations [16, 17]. Wang et al [18] also revealed metabolic abnormalities during NPC serum study by NMR spectroscopy. However, neither the underlying metabolism that is characteristic of NPC cell differentiation has not been deeply investigated nor the relationship between differentiation degree and metabolism in cells has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The significant correlation between metabolites of phosphatidylcholine (betaine, choline, trimethylamine-N-oxide) and individuals who experienced myocardial infarction, stroke, or death has been found also by Wang et al [39]. Positive correlation of betaine levels and inflammation is mentioned by ECLIPSE study [40].…”
mentioning
confidence: 71%
“…The association of circulating TMAO levels with cancer is more variable and is dependent on cancer type. Low serum concentrations of TMAO have been associated with nasopharyngeal carcinoma patients 178 and renal cell carcinoma, with levels increasing post-nephrectomy. 186 In contrast, higher levels of serum or plasma TMAO have been reported for primary liver cancer patients (sex-and age-adjusted odds ratio of 3.43), 180 oral squamous cell carcinoma, 348 cancer.…”
Section: Cancermentioning
confidence: 99%
“…The association of circulating TMAO levels with cancer is more variable and is dependent on cancer type. Low serum concentrations of TMAO have been associated with nasopharyngeal carcinoma patients and renal cell carcinoma, with levels increasing post-nephrectomy . In contrast, higher levels of serum or plasma TMAO have been reported for primary liver cancer patients (sex- and age-adjusted odds ratio of 3.43), oral squamous cell carcinoma, and colorectal cancer. , In the case of pancreatic cancer, contradictory results have been published, with one study finding significantly lower serum TMAO concentrations in patients and another reporting that higher concentrations of TMAO were associated with risk for pancreatic cancer …”
Section: Disease States and Disordersmentioning
confidence: 99%